Deep Brain Stimulation in Sub-Thalamic Nucleus in idiopathic Parkinson’s disease – our initial experience in four cases (Bangladesh Journal of Neurosurgery, 2019)
Parkinson’s Disease ( PD ) is a chronic neurodegenerative disease . It’s cardinal features are resting tremor, Rigidity, Akinesia and postural instability. Idiopathic Parkinson’s disease develops mainly due to degeneration of Dopaminergic neurons of Substantia Nigra. The role of Subthalamic Nucleus ( STN ) in the development of Parkinsonian Tremmor and other cardinal features is not completely understood yet. However previous studies in monkeys , administration of MPTP ( 1-methyl-4-phenyl- 1.2.3.6.-tetrahydropyridine ) proved that sub thalamic nucleus has a direct role in the development of Parkinsonian tremor and other features. We used no Micro Electrode Recording (MER) system,only studied clinically that Parkinsonian tremor stopped immediately after placement of electrode and same thing happened after micro stimulation of the sensorymotor region of the sub thalamic nucleus .Then high frequency deep brain stimulation ( DBS ) of these same four patients were assessed six months after surgery which led to a significant reduction of Parkinsonian tremor as well as other cardinal features of PD ( p< 0.001 ) . Both postural and resting tremor disappeared completely in three cases and significantly reduced in one caseBang. J Neurosurgery 2019; 9(1): 78-83